A new look at molecular biology of breast cancer. Issue 1 (2nd January 2019) - Ma, Chi; Nepal, Manoj; Kim, Jin-Hee; Fan, Ping; Fei, Peiwen
ABSTRACT: In the past 25 years, incidence rates of breast cancer have risen about 30% in westernized countries. Mutations in BRCA1 and BRCA2 are the most prominent cause of breast cancer. However, these cancer susceptibility genes (BRCAs) only account for a few percent of women suffering breast tumor. With our understanding that BRCAs are Fanconi Anemia (FA) genes, investigations into the FA signaling network should provide a previously unrecognized key to unlock in-depth insights into both etiology and treatment of breast cancer. Here, we discuss utilization of the FA signaling as a unique genetic model system to expand our knowledge about the molecular biology of breast cancer and potential applications of the gained knowledge to enable preventive and therapeutic approaches for breast cancer patient care.